PENGARUH SERVICE RECOVER TERHADAP KEPUASAN PELANGGANSPEEDY: THE EFFECT OF SERVICE RECOVERY ON SPEEDY’S CUSTOMER SATISFACTION - Raja Sharah; Eka Priadi (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study purpose is to explain the Service recovery on Telkom Speedy, and the influence of service recovery on customer satisfaction. Sample are students of faculty of economics and business of University of Jambi which consist of of 80 respondents that chousen with purposive techniques. The study result shows significant influance of distributive justice (0,000) and interactional justice (0,052), but it is insignificant for procedural justice (0,112) to customer satisfaction. Hence, service recovery has important role to create customer satisfaction mainly in case of service fault. Keywords: Service Recovery, Distributive Justice, Procedural Justice, Interactional Justice, Customer Satisfaction.